Braking Performance and Response Analysis of Trains on Bridges Under Seismic Excitation - Yuanqing Lu; Xiaonan Xie; Hongkai Ma; Ping Xiang (Applied Sciences, 2025)
Earthquakes can trigger emergency braking in urban rail systems, yet the combined effect of braking and ground motion on train–bridge safety remains poorly quantified. Using the Wuxi Metro Line S1 (160 km/h initial speed) on a ten-span simply supported bridge as a case study, we build a multi-body dynamic subway model coupled to a finite element track–bridge model with non-linear Hertz wheel–rail contact. Under the design-basis earthquake (PGA ≈ 0.10 g), the train’s derailment coefficient and lateral car body acceleration rise by 37% and 45%, while the bridge’s lateral and vertical accelerations increase by 62% and 30%, respectively. Introducing a constant emergency brake deceleration of 1.2 m/s2 cuts those train-side peaks by 20–25% and lowers the bridge’s lateral acceleration by 18%. The results show that timely braking not only protects passengers but also mitigates seismic demand on the structure, offering quantitative guidance for urban rail emergency protocols in earthquake-prone regions.